Distribution Of Plankton Community On Surface, Middle, And Bottom Waters In Danau Dua Rasa Labuan Cermin Biduk-Biduk, Berau, East Kalimantan - Muhammad Rizaldi; Muhamad Yasser; Lily Inderia Sari; Aditya Irawan; Omega Raya Simarangkir (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Plankton as a basic component in the structure of life in the waters, spesifically as water producers can be used as one of the parameters in monitoring the quality of the aquatic environment. The existence of aquatic tourism activities and quantitative and qualitative plankton can be used to determine the fertility of a waters, by measuring the abundance and distribution of plankton found at each depth. The research station is divided into three sites, site A is the source of the entry and exit of sea water, site B is in the middle of the lake, and site C is located close to the freshwater spring. Based on the results of research in the waters of Danau Dua Rasa Labuan Cermin, 8 classes of plankton were obtained with 24 species, there are the Chlorophyceae, Cyanophyceae, Chrysophyceae, Dinophyceae, Mastigophora, Crustacea classes. Sarcodina and Rotatoria. The Danau Dua Rasa Labuan Cermin are included in the Mesotrophic waters group. Because the abundance value reaches 9,513 ind/L, in other words, Labuan Cermin waters have a moderate fertility level that can support the breeding and survival of aquatic organism and the continuity of a good photosynthesis process.